THE UTILIZATION OF EXPRESSIVE WRITING IN COUNSELING IN INDONESIA - Nur'aini Safitri; Nurhafiza (EDUCATIONE, 2026)
Expressive Writing is a therapeutic technique that encourages individuals to explore their thoughts, emotions, and experiences through writing. This technique is especially beneficial for individuals who have difficulty expressing themselves or expressing their problems verbally in the counseling process. This study uses the literature review  method with the aim of finding out the use of expressive writing in counseling in Indonesia. Data collection was carried out by conducting a review of various literature relevant to the research study using the keywords "expressive writing", "counseling", and "Indonesia" in proquest.com, ebsco. com, and scholar.google.com in the last five years which were then analyzed using content analysis and the results were presented descriptively. The results of the study show that the use of expressive writing in counseling in Indonesia is used in information services, group guidance, group counseling, and individual counseling to develop the ability to manage anger, emotions, reduce anxiety, aggressiveness, overcome learning saturation, anxiety, self acceptance, and improve career planning in students. Counselors can utilize expressive writing in counseling both individually, in groups, or in classics to help alleviate problems experienced by students in school.